ISLAMISASI ILMU PENGETAHUAN: SEBUAH TAWARAN - Ahmad Suyuthi (Al Hikmah: Jurnal Studi Keislaman, 2014)
The idea of Islamization of knowledge or rather Islamization of contemporary science the come from the premise that contemporary science is not value free and universal. M. Naquib Al-Attas which has as the originator of the concept of Sciences Islamization before the idea was popularized by Ismail al-Faruqi, explains that modern science was strongly influenced by religious views, culture, and philosophy, which reflects the awareness and experience of the West. For this reason that contemporary science can not be adopted out without sibghah with Islamic values.Islamization of knowledge tasks according to Al-Attas will include a critical test of modern scientific methods, concepts, estimates, symbols, empirical and rational aspects, and what about the values and ethics, interpretation of the origins , theory of knowledge, estimates of the external world, the uniformity of nature, and the rationality of natural processes, as well as his theory of the universe, classification of science, the limits and mutual relations between science and its relationship with other social relations.Meanwhile, according to Al-Faruqi, Islamization can be achieved through the incorporation of new science into the realm of Islam by removing, managing, analyzing, interpreting and over, and customize it according to Islamic values and views. According to the issues above, Al-Attas offers the concept of Islamization of knowledge (in Islamic education) as the accumulation of knowledge because of epistemological problem has been greatly influenced by the West. Influence Western epistemology that secularized, especially in the field of education has brought the destructive implications for the community, hence the offer that is soluteve thought to be things that are necessary.